2017
DOI: 10.1093/cz/zox011
|View full text |Cite
|
Sign up to set email alerts
|

Urban health and ecology: the promise of an avian biomonitoring tool

Abstract: Urban-dwelling birds have the potential to serve as powerful biomonitors that reveal the impact of environmental change due to urbanization. Specifically, urban bird populations can be used to survey cities for factors that may pose both public and wildlife health concerns. Here, we review evidence supporting the use of avian biomonitors to identify threats associated with urbanization, including bioaccumulation of toxicants and the dysregulation of behavior and physiology by related stressors. In addition, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 97 publications
(129 reference statements)
1
20
0
1
Order By: Relevance
“…Considerable extent of taxonomic and functional diversity of birds was observed across the urban-rural gradient with prominent differences in the rural against the urban areas. Such observations tally with the characteristic bird species assemblages in urban areas (Pollack et al 2017, Rodriguez et al 2018, Filloy et al 2019 and the differences in the urban and rural context (Sengupta et al 2014, Kale et al 2018a, 2018b, Pal et al 2019. In the present study, higher diversity and species richness were observed in thesuburban and rural station areas than that of urban areas.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Considerable extent of taxonomic and functional diversity of birds was observed across the urban-rural gradient with prominent differences in the rural against the urban areas. Such observations tally with the characteristic bird species assemblages in urban areas (Pollack et al 2017, Rodriguez et al 2018, Filloy et al 2019 and the differences in the urban and rural context (Sengupta et al 2014, Kale et al 2018a, 2018b, Pal et al 2019. In the present study, higher diversity and species richness were observed in thesuburban and rural station areas than that of urban areas.…”
Section: Discussionsupporting
confidence: 86%
“…Birds are one of the most suitable species to monitor the short and the long-term environmental changes (Koskimies 1989, Bibby 1999, Khan & Naher 2009. Use of birds as indicators for habitat conditions (Canterbury et al 2000, Browder et al 2002,Vallecilo et al 2016, including forests (Pain et al 2004, Venier & Pearce 2004, Aich & Mukhopadhyay 2008, Chatterjee et al 2014, agro-ecosystems (Dhindsa & Saini 1994, Borad et al 2001, Basavarajappa 2006, Sundar & Kittur 2013, Hossain & Aditya 2016 and aquatic bodies (Kumar et al 2006, Kumar & Gupta 2013, biological diversity (Gregory et al 2003, Fraixedas et al 2020 and urbanization (Pollack et al 2017) are well-recognized, apart from the application of birds as flagship species in conserving diversity (Williams et al 2000) and enhancing tourism (Veríssimo et al 2009). Due to an increasing appreciation of the ecosystem services provided by the birds (Whelan et al 2008(Whelan et al , Şekercioğlu 2012a(Whelan et al , 2012b, the focus for the monitoring, conservation and ecological studies on birds are continued at different biogeographical context (Bradford et al 1998, Browder et al 2002, Lee et al 2004, Sundar & Kittur 2013, Hossain & Aditya 2016.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, diet [44][45][46][47][48][49][50], foraging mode and strata [51][52][53], and the location of breeding and resting places [44][45][46]48,54] influence whether a species is able to live in a particular urban area. Another important factor to consider is pollution, including noise and light [55][56][57][58][59][60][61]. Thus, even if a developer is willing to create conditions suitable for a species, the species may be too sensitive against disturbances to survive in the urban area.…”
Section: Local Species Potential: Site Limitations and Dispersal Barrmentioning
confidence: 99%
“…Birds have the potential also to serve as powerful biomonitors and can be used to survey for factors that may pose both public and wildlife health concerns (Pollack et al, 2017).…”
Section: Accepted Manuscriptmentioning
confidence: 99%